PEMBUATAN TATA LETAK BUKU BIOGRAFI BERJUDUL “SUHARTATIK KONTRIBUSI DALAM PENINGKATAN KUALITAS PENDIDIKAN DI JAWA TIMUR” KARYA Dr. MUSTAKIM, S.Si., M.Si. - Rumekso, Kunto Adi (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2025)
Awards for someone's performance and inspiring life are best realized in a biography. The biography of Mrs. Suhartatik, a modern Kartini who has contributed to improving the quality of education in East Java Province, was written by Dr. Mustakim, S.Si., M.Si. This is a fitting tribute, with the hope that it will serve as a medium to record the life story of Mrs. Suhartatik so that it will be immortalized in writing and can be read by current and future generations. The author had the opportunity to assist in designing the layout of a beautiful work that responds to the noble performance of the field of education, as a means of supporting efforts to achieve the national goal of developing superior, characterful, and wise human resources for a much better future for the nation through quality education.